Extended Triple Bottom Line Theory for A New Framework of Divinity Environmental Accounting with Local Genius Catur Brata PeNyepian - I Putu Mega Juli Semara Putra; I Made Narsa (Jurnal Ilmiah Akuntansi, 2022)
This paper aims to present an environmental accounting framework based on divinity. The framework is built by combining the triple bottom line (TBL) theory, which is commonly used, and the Tri Hita Karana (THK) derived from local wisdom in Bali so that a new framework is formed. This paper discusses Catur Brata PeNyepian (CBP) as an implementation of the THK to study how Bali's local culture can be used by companies and the world in implementing environmental accounting. Data analysis was carried out by conducting interviews with informants who had understanding, practice, and policymakers in Bali. The opinions of the informants are then discussed, and conclusions are drawn. The implication of this paper is to produce a new framework for environmental accounting that is more complete with divine elements.